Economic reform and state-owned enterprises in China 1979 - 1987 (Studies on contemporary China, 1994)
Economic Reform and State-Owned Enterprises in China is a comprehensive and detailed investigation into China's reform process during the period 1979 to 1987, with especial reference to the effect of the reforms on the industries (mostly large-scale) that are still owned by the state. The data on which this book is based resulted from a statistical survey and questionnaire of the managers of approximately 380 enterprises, documenting their responses to the new environment created by the reforms